Ceratobasidium sp isolates from native orchid species of Western Ghats, India support enhanced growth of Phalaenopsis hybrid seedlings - Suresh, Lekshmi; S, Shailajakumari; Decruse, S. William (Plant Science Today, 2024)
Mycorrhiza-assisted cultivation of orchid seedlings has immense potential for enhanced growth and adaptability of orchids to facilitate conservation and cultivation with minimum application of nutrients and plant protection chemicals. Phalaenopsis hybrids are highly attractive and cultivated mostly as potted orchid plants and are prone to several fungal pathogens. The present study evaluates the effect of 4 orchid symbionts in combination with NPK fertilizer on the seedling growth of symbiotic seedlings of Phalaenopsis white and day-star hybrids under ex-vitro conditions. Four fungal isolates viz., Ceratobasidium_Wyd2 (MW595786; MTCC13384), Ceratobasidium_Idk (MW595787: MTCC13383), Ceratobasidium_Vs1 (OL374050; MTCC13377) and Ceratobasidium _Vs2 (OL374052: MTCC13378) grown on sterilized coir pith medium for 10 days and were transferred onto earthen pots for planting of seedlings. One-year-old seedlings used for the study possessed an average 2.70 g fresh weight. On conclusion of the experiment, after 6 months, the seedlings of day-star hybrid grown in the presence of both fungus and NPK fertilizer exhibited enhanced growth compared to either of them applied individually. The highest weight gain was supported by VS1 (12.4±1.8 g) followed by VS2 (10.7± 4.6 g) and Wyd2 (9.8±1.7 g). Those fungi also supported appreciable growth individually, giving 6.5±3.1, 6.9±2.2, and 6.5±0.8 g weight gain respectively. If the nutrient alone was applied, the weight gain was very low (2.8±0.9 g) nearly equal to control (1.8±1.8 g) without having fungi or nutrients. The mycorrhizae re-isolated from the roots of seedlings exhibiting enhanced growth were confirmed as Vs1 and Vs2 through sequencing of the ITS region. Formulation of a potting medium including Ceratobasidium species isolates VS1 and VS2 is thus possible to grow Phalaenopsis seedlings to get enhanced growth.